Expression of Phosphorylated AMP-Activated Protein Kinase Predicts Response to Transarterial Chemoembolization in Postoperative Cases of Hepatocellular Carcinoma. Issue 11 (March 2016) - Zheng, Long-Yi; Wu, Lu; Lu, Jin; Zou, Da-Jin; Huang, Qin
Abstract : Abstract: Hepatocellular carcinoma (HCC) is one of the most prevalent malignancies in the world. Transcatheter arterial chemoembolization (TACE) was commonly used for HCC patients postoperatively. However, the survival benefits of adjuvant TACE were controversial due to the extensive heterogeneity of HCC. Hence, there is a critical need to explore potential biomarkers that can predict the clinical response to TACE. The AMP-activated protein kinase (AMPK) is a highly conserved heterotrimeric serine/threonine kinase that plays a central role in linking metabolism and cancer development. In this study, we aimed at evaluating the association of pAMPKα (Thr172) status with clinical outcomes in HCC patients treated with or without postoperative adjuvant TACE. pAMPKα (Thr172) expression was assessed using immunohistochemical analysis in a cohort of 378 Chinese HCC patients who had undergone tumor resection. Kaplan–Meier analysis and multivariate Cox proportional hazards models were used to study the impact on clinical outcomes. High pAMPKα (Thr172) expression was associated with improved disease-free and overall survival and was an independent prognostic factor for overall survival by multivariate analysis. Furthermore, low pAMPKα (Thr172) expression level was correlated with high percentage of OV6 + tumor-initiating cells (T-ICs) in HCC specimens. To our knowledge, it can be demonstrated for the first time that pAMPKα (Thr172) status is associated with response to postoperative adjuvant TACE. High pAMPKα (Thr172) level in HCC may serve as a positive predictor of survival in HCC patients undergoing TACE.